2011
DOI: 10.3109/10408444.2011.558487
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of key evidence on the human health hazards of exposure to bisphenol A

Abstract: Despite the fact that more than 5000 safety-related studies have been published on bisphenol A (BPA), there seems to be no resolution of the apparently deadlocked controversy as to whether exposure of the general population to BPA causes adverse effects due to its estrogenicity. Therefore, the Advisory Committee of the German Society of Toxicology reviewed the background and cutting-edge topics of this BPA controversy. The current tolerable daily intake value (TDI) of 0.05 mg/kg body weight [bw]/day, derived b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
168
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(184 citation statements)
references
References 160 publications
2
168
1
4
Order By: Relevance
“…A recently published paper reviewed more than 5000 safety-related studies, concluding that exposure to bisphenol-A represents no noteworthy risk to the health of the human population [29]. However, in vitro data suggested that bisphenol-A could display some effects on the immune system: it has been shown to inhibit the synthesis of monocyte-chemoattractant protein (MCP) -1 in a tumor cell line, with a potency three times greater than that of E2 [30].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…A recently published paper reviewed more than 5000 safety-related studies, concluding that exposure to bisphenol-A represents no noteworthy risk to the health of the human population [29]. However, in vitro data suggested that bisphenol-A could display some effects on the immune system: it has been shown to inhibit the synthesis of monocyte-chemoattractant protein (MCP) -1 in a tumor cell line, with a potency three times greater than that of E2 [30].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…BPA is readily released from these products into food and water, and hence contributes to human exposure through diet or drinking water (Hengstler et al, 2011;Michałowicz, 2014). Bio-monitoring studies have reported that BPA can be detected in over 90% of blood, urine and other tissue samples around the world (Vandenberg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The resultant LOD and LOQ were 0.0012 and 0.004 ng/mL, respectively. Standard and spiked samples at three different BPA concentration (1, 10, 100 ng/mL) were extracted range of 0.05-3.0 ng/mL [1][2][3][4][5][6][7]. Our data has shown that similar level of BPA is into purified water.…”
Section: Extraction Methods and Lc-ms/ms Analysismentioning
confidence: 59%
“…Analyses were performed in the multiple reaction monitoring (MRM) mode and negative ionization. The product ions at 133.2 m/z and 212.1 m/z for BPA and at 138.2 m/z and 215.0 m/z for d 6 -BPA (IS) were monitored to assess unambiguous identification. The linearity of the detector response was verified over the concentration range 0.100-200 ng/mL.…”
Section: Extraction Methods and Lc-ms/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation